Bank Performance Based on Core Capital Amid the COVID-19 Pandemic in Indonesia - Susilowati, Fitri; Purnama, Hari (KnE Social Sciences, 2022)
COVID-19 has had an impact on banking, liquidity and credit. The Financial Services Authority (OJK) has tried to mitigate some of these effects with countercyclical policies as stated in OJK regulation number 11/POJK.03/2020. It is however unclear whether the policy can reduce banking risk in the midst of easing or relaxation policies. This research employed secondary data taken from the Indonesian banking statistics published by OJK. Indicators of bank performance used in the study referred to the policies of the OJK and comprised: capital adequacy ratio, core capital ratio to riskweighted asset, return on assets ratio, operational efficiency ratio, net interest margin ratio, loans to deposits ratio, and liquid assets ratio. The performance index analysis was divided into two periods: January 2017- February 2020 and March 2020 - February 2021. The period was divided to determine the quality of bank performance before and after the stipulation of restructuring policy. The index calculation was carried out by determining the weight based on the dimensions (bank performance indicators). The weight given to each of these indicators was conformed to all indicators. The analysis of the bank performance used the composite index of development calculation. Based on the results, the availability of bank capital affected financial performance. The implementation of countercyclical policies had an impact on bank performance in banks that had greater availability of capital. Banks can evaluate and improve strategies in countercyclical implementation to support national economic recovery. Keywords: core capital, CAR, CCR to RWA, ROA, OER, NIMR, LDR